PERBANDINGAN STRATEGI PEMBELAJARAN AKTIF TIPE EVERYONE IS TEACHER HERE DAN TIPE TRUE OR FALSE TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS X SMAN 3 LENGAYANG - Mayuni, Sri - (Pendidikan Biologi, 2014)
Low of learning biology outcomes is a matter of students in SMAN 3 Lengayang. It can be seen from the average value of the students daily tests are still under the passing grade criteria (KKM) which is 75 in environmental contamination material at X class in SMAN 3 Lengayang at second semester in academic year 2012/2013. This research is aimed to determine the differences about active learning strategies with Everyone is Teacher Here and True or False type to the learning biology outcomes at X Class students in SMAN 3 Lengayang. This research is an experimental research by using a randomized design post test-only comparison group design. The population is the all of students at X class in SMAN 3 Lengayang. Sampling in this research is purposive sampling with X.D class as first experimental class and X. E class as second experimental class. The instrument used is students learning biology outcomes sheet test. The data is analyzed by using t-test. Based on the analysis of the final test, the results obtained the differences students learning biology outcomes in those classes. The average value of the first experimental class is 70.5 with not too high and second experimental class is 67.2. T-test results obtained t = 1.53 and table = 1.67. So, it can be concluded that there is no significant differences in students learning biology outcomes between active learning strategy with Everyone is Teacher Here and True or False type at X Class in SMAN 3 Lengayang.